Research on factors affecting the application of management accounting in Vietnamese construction enterprises - Hau, Nguyen Van; Tu, Chuc Anh; Trinh, Nguyen Thi Diem; Anh, Nguyen Thien Phuc; My, Nguyen Huyen (Asian Economic and Financial Review, 2025)
In Vietnam’s growing economy, construction enterprises (CEs) play a crucial role in establishing infrastructure and fostering the development of other industrial sectors. However, CEs also face significant challenges, particularly in managing costs, schedules, and quality within projects. The adoption of management accounting (MA) has become an indispensable tool for CEs to optimize financial operations, enhance managerial efficiency, and support strategic decision-making. Investigating the factors influencing MA adoption in Vietnamese CEs is a critical issue. The influencing factors considered include: firm size, technological level, accountants’ qualifications, top management perception, the cost of organizing the MA system, and the level of market competition. This paper aims to identify and analyze the factors affecting MA adoption in CEs, employing a mixed-methods approach (qualitative and quantitative) through surveys targeting individuals from the board of directors, chief accountants, or accounting managers within the enterprises. SPSS and AMOS quantitative results have identified factors affecting the application of MA and the level of influence of each factor. The research findings will clarify the direction and extent of each factor’s impact, thereby proposing practical implications and solutions to enhance MA adoption in Vietnamese CEs.